Lagrangian particle tracking at large Reynolds numbers - Küchler, Christian; Ibanez Landeta, Antonio; Moláček, Jan; Bodenschatz, Eberhard (Review of scientific instruments, 2024)
In the study of fluid turbulence, the Lagrangian frame of reference represents the most appropriate methodology for investigating transport and mixing. This necessitates the tracking of particles advected by the flow over space and time at high resolution. In the past, the purely spatial counterpart, the Eulerian frame of reference, has been the subject of extensive investigation utilizing hot wire anemometry that employs Taylor’s frozen flow hypotheses. Measurements were reported for Taylor scale Reynolds number Rλ > 104 in atmospheric flows, which represent the highest strength of turbulence observed on Earth. The inherent difficulties in accurately tracking particles in turbulent flows have thus far constrained Lagrangian measurements to Taylor scale Reynolds numbers up to approximately Rλ = 103. This study presents the Lagrangian particle tracking setup in the Max Planck Variable Density Turbulence Tunnel (VDTT), where Taylor scale Reynolds numbers between 100 and 6000 can be reached. It provides a comprehensive account of the imaging setup within the pressurized facility, the laser illumination, the particles used, and the particle seeding mechanism employed, as well as a detailed description of the experimental procedure. The suitability of KOBO Cellulobeads D-10 particles as tracers within the VDTT is illustrated. The results demonstrate that there is no significant charge exhibited by the particles and that the impact of their inertia on the results is negligible across a wide range of experimental conditions. Typical data are presented, and the challenges and constraints of the experimental approach are discussed in detail.